Bone acrometastasis: case report and literature review - Linares Restrepo, Francisco; Restrepo-Jaramillo, José Simón; Aguilar, Francisco Javier (Revista Cubana de Ortopedia y Traumatología, 2025)
Acrometastases are metastatic lesions located distally at the elbow and knee. They are rarely found in the hands and feet. A 50-year-old patient with metastatic renal cell carcinoma and lesions at this level is presented, along with the management and results.